2008
DOI: 10.1007/s10750-008-9396-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and behavioural influences on juvenile fish migrations in regulated rivers: a review of experimental and field studies

Abstract: This paper reviews results of experimental and field studies of downstream migration of young fish carried out in the Institute of Ecology and Evolution (Russian Academy of Sciences) as a part of the research programme on fish behaviour and ecology. Studies of fish migrations have been dominated by descriptions of migratory routes and proximate control of orientation. Behaviour and ecological factors influencing variability of downstream migrations of fish larvae and fry are still poorly understood. Life cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 41 publications
4
110
1
Order By: Relevance
“…Result of the sensitivity analysis for selected parameters of the RCRW model regarding the transformed longitudinal and lateral coordinates and , in combination with the error measures over-reorientation (oRe) and error in the desired movement direction (EM). dent on diel patterns characterized by a nocturnal increase in drift, could neither be sufficiently proved nor disproved in our study, whereas other studies support the concept of a diel impact on larval downstream movement (e.g., Copp et al 2002;Zitek et al 2004;Pavlov et al 2008). In light of these proven impacts on movement patterns, a stagespecific and RCRW model, using flow velocity-dependent fractions of movement patterns f U,M , has been developed in combination with a relatively smooth transition of the fitted lognormal distributions concerning durations of movement sequences ⌬t j,M,U between flow velocity classes.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Result of the sensitivity analysis for selected parameters of the RCRW model regarding the transformed longitudinal and lateral coordinates and , in combination with the error measures over-reorientation (oRe) and error in the desired movement direction (EM). dent on diel patterns characterized by a nocturnal increase in drift, could neither be sufficiently proved nor disproved in our study, whereas other studies support the concept of a diel impact on larval downstream movement (e.g., Copp et al 2002;Zitek et al 2004;Pavlov et al 2008). In light of these proven impacts on movement patterns, a stagespecific and RCRW model, using flow velocity-dependent fractions of movement patterns f U,M , has been developed in combination with a relatively smooth transition of the fitted lognormal distributions concerning durations of movement sequences ⌬t j,M,U between flow velocity classes.…”
Section: Discussioncontrasting
confidence: 96%
“…In accordance with Zens et al (2017), we found that for higher flow conditions -corresponding to higher velocity classes in our study and higher flow scenarios in Zens et al (2017) -Au movement was lower and Ap movement was dominant. Also, in accordance with other studies (Lechner et al 2014b;Schludermann et al 2012;Pavlov et al 2008), we found highly significant larval stage-specific differences (L2, L4) in the fractions of movement patterns for Au and P movements. Thus hypothesis (b), that movement patterns are dependent on larval developmental stage and concomitant changes in swimming ability, is confirmed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For each event of downstream movement, the proper movement rate (relative to water flow; V f ) was calculated according to Pavlov et al (2008) as…”
Section: Determined Variables Movement Patterns and Displacementmentioning
confidence: 99%
“…Our work is based on the fundamental concept of Pavlov et al (2008), who proposed three different types of downstream dispersal of riverine fish larvae based on swimming activity and orientation of larvae: passive drift (P), active downstream (Ad) movement, and an intermediate type, active-passive (Ap) downstream movement. Beyond these, active upstream (Au) and lateral movements are also assessed in the present study, and the effects on displacement distances are evaluated.…”
Section: Introductionmentioning
confidence: 99%